O setor farmacêutico no Brasil sob as lentes da conta-satélite de saúde - Fabiola Sulpino Vieira; Maria Angelica Borges dos Santos (Instituto de Pesquisa Econômica Aplicada (IPEA), 2020)
– This text aims to describe the pharmaceutical sector in Brazil using information from the satellite health account (CSS) and, based on this information, to discuss aspects related to the development and production of medicines in the country. In this work, the pharmaceutical sector is defined as a branch of the economy that brings together the set of activities involved in the production, marketing and transportation of pharmaceutical chemicals, medicines and pharmaceutical preparations. As in CSS the focus is on products, regardless of the economic activity responsible for their production, the use of information from this satellite account results in a more comprehensive view of this sector in the country. To this end, data on supply, demand, value added and occupations from 2010 to 2017 were obtained from the publication of the CSS and the complementary material made available by the Brazilian Institute of Geography and Statistics (IBGE) on its website (supply and use tables). CSS data and information reveal an increasing scenario of Brazilian external dependence on the import of pharmaceuticals, medicines and pharmaceutical preparations, which means weakening the activity of manufacturing pharmaceutical products, and expanding the activity of pharmaceutical trade. This picture indicates the need to strengthen industrial policies aimed at the sector, in order to reduce Brazilian external dependence, especially on products with higher added value. The covid-19 pandemic has spelled out the vulnerability of countries that depend on the import of health technologies. It has sparked debate about the repositioning of the production of these technologies worldwide. In this context, it is essential that the State makes efforts to increase the presence of the pharmaceutical industry and health products industries in the national territory. And, it is also important to foster the technological capacity of the official pharmaceutical laboratories, which could play a more strategic role in the Brazilian public health system.
Keywords: E20; H51; 330; health economics; drug industry; pharmaceutical services; production of products; health expenditures; occupations